INTERNALISASI PENDIDIKAN KARAKTER MELALUI PROGRAM PEMBIASAAN MEMBACA ASMAUL HUSNA DI SEKOLAH DASAR - Ely Sholihah; Firman Robiansyah; Darmawan Darmawan (PGSD Universitas Muhammadiyah Cirebon, 2022)
The depravity of the nation's children can be seen from the manners that are currently starting to fade, it can be observed from the way they talk to others, teachers, and even their parents, dirty sentences that should not be spoken often, dishonest nature, and good morals in people. a child who is hard to find. Therefore, of course, you must make an effort in handling and even control these events so that they do not become a child's culture. One effort that can be done is to familiarize children with good deeds. From these habits, it is hoped that the values ??of good character that are embedded in children will grow. This study aimed to determine the process of habituation and the value of the characters in the habit of reading Asmaul Husna at SD Negeri Umbul Kapuk. This research is research that uses a qualitative approach with case study research methods and the types of auxiliary instruments used are observation, interview sheets, and documentation. From the results of the analysis conducted by the researchers, the character building of students through the method of habituation of reading Asmaul Husna at SD Negeri Umbul Kapuk includes religious, love to read, responsibility, discipline, independence, friendly/communicative, social care, love peace, tolerance, and curiosity. Keywords: Character, Habituation, Student, Asmaul Husna, Elementary school